2020
DOI: 10.1016/j.jamcollsurg.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Does Vertical Integration Improve Access to Surgical Care for Medicaid Beneficiaries?

Abstract: BACKGROUND: Vertical integration is increasingly common among surgical specialties in the US; however, the effect of vertical integration on access to care for low-income populations remains poorly understood. We explored the characteristics of surgical practices associated with vertical integration and the effect of integration on surgical access for Medicaid populations. STUDY DESIGN: Using a survey of US office-based physician practices, we examined characteristics of 15 surgical subspecialties from 2007 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…These experiences have yielded positive outcomes that align with the results anticipated for the Portuguese reform. One illustrative study is the research conducted by Haddad et al [41], which determined that there is a correlation between the association of primary surgical and procedural practices with hospitals and an enhanced accessibility to surgical care for Medicaid patients, in comparison to traditional models. Similarly, a study conducted by Gillies et al [42] found that the integration of hospitals and physicians' practices yields superior outcomes in terms of the processes of care quality measures such as breast cancer screening, adolescent immunisation screening, and the management of high blood pressure when compared to non-integrated models.…”
Section: Resultsmentioning
confidence: 99%
“…These experiences have yielded positive outcomes that align with the results anticipated for the Portuguese reform. One illustrative study is the research conducted by Haddad et al [41], which determined that there is a correlation between the association of primary surgical and procedural practices with hospitals and an enhanced accessibility to surgical care for Medicaid patients, in comparison to traditional models. Similarly, a study conducted by Gillies et al [42] found that the integration of hospitals and physicians' practices yields superior outcomes in terms of the processes of care quality measures such as breast cancer screening, adolescent immunisation screening, and the management of high blood pressure when compared to non-integrated models.…”
Section: Resultsmentioning
confidence: 99%
“…Despite that, even in these circumstances vertical integration has shown some benefits. In a systematic review of vertical integration and quality of care in the US, 6 out of 10 studies found that vertical integration was associated with higher quality of care ( 22 ) and vertical integration was associated with increased access to surgical care for vulnerable, low-income patients ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research on vertical integration extends beyond its impact on staff satisfaction. A study examining access to surgical care for Medicaid beneficiaries found that vertical integration is associated with increased Medicaid acceptance rates among practices, allowing greater access to surgical care for vulnerable, low-income patients [ 49 ]. Similarly, other studies suggest that vertical integration has the potential to reduce hospital readmissions [ 50 51 ].…”
Section: Discussionmentioning
confidence: 99%